Turkish validity and reliability study of the cyber pornography use inventory-9 - Ünübol, Hüseyin; Ünübol, Başak; Tutgun Ünal, Aylin; Hızlı Sayar, Gökben (Journal of Dependence, 2023)
Objective: The aim of this study is to examine the language equivalence, validity and reliability of the Turkish version of the Cyber Pornography Use Inventory-9 (CPUI-9) developed by Grubbs et al. Method: CPUI-9 was applied to a study group consisting of 4390 people throughout Turkey. The Inventory is rated on a seven-point Likert scale, ranging from "Strongly Disagree" to "Strongly Agree," and measures individuals’ level of cyber porn use. As a result of the Pearson correlation coefficients made to examine the compatibility between the English and Turkish forms of CPUI-9, positive and significant values were reached. Results: The factor analysis performed to ensure the construct validity of the Inventory, which initially consisted of 3 factors, the same structure was revealed in the Turkish form. The first factor, "Perceived Difficulty," explained 47.57% of the variance, the second factor, "Emotional Distress," 24.23%, and the third factor, "Access Efforts," explained 10.72% of the variance. The three-factor structure consisting of 9 items explained 82.53% of the total variance. In addition, three factors confirmed CPUI-9 in the confirmatory factor analysis. The goodness of fit values was found to be acceptable (Chi-square/freedom value: 3.97; RMSEA: 0.08; NFI: 0.95; NNFI: 0.93; CFI: 0.96; GFI:0.94; AGFI: 0.90). The Cronbach Alpha value of the internal consistency coefficient of the scale was found to be 0.84. Conclusion: Turkish version of the CPUI-9 Inventory is both valid and reliable and can be utilized as a dependable and accurate measurement tool.